Impact of potato business on household food security: An empirical study from Tigray regional state, Ethiopia - Aregawi Beyene Bsrat; Kebede Manjur Gebru; Tekleyohannes Hailekiros Ayele; Goitom Gebrehiwot Lema (Journal of Agriculture and Rural Development in the Tropics and Subtropics)
Food insecurity remains a persistent global challenge, particularly in sub-Saharan Africa. However, the role of cash crops in influencing household food security continues to be debated. To address this gap, this study examines the impact of potato cash crop production on household food security in the Atsbi Wonberta District of Tigray Regional State, Ethiopia. A comprehensive survey of 173 households was conducted. The study employed a binary probit model to analyze factors influencing farmers’ participation in potato production and used propensity score matching to assess the impact of this participation on food security. The results show that factors such as oxen ownership, educational attainment, access to irrigated land, and training opportunities were positively associated with farmers’ involvement in potato production. Furthermore, participation in potato production significantly improved household income and food security. Based on these results, the study recommends the implementation of capacity-building initiatives, including targeted training programmes for smallholder farmers. In addition, governments and stakeholders should prioritise investment in rural infrastructure and irrigation development to increase the positive impact of potato production on household food security.